Native Peoples of North America - Stebbins, Susan (Open textbook library., 2013)
Native Peoples of North America is intended to be an introductory text about the Native peoples of North America (primarily the United States and Canada) presented from an anthropological perspective. As such, the text is organized around anthropological concepts such as language, kinship, marriage and family life, political and economic organization, food getting, spiritual and religious practices, and the arts. Prehistoric, historic and contemporary information is presented. Each chapter begins with an example from the oral tradition that reflects the theme of the chapter. The text includes suggested readings, videos, and classroom activities. This text was updated September 2019; the changes are detailed in an errata section in the text.